PERCEPTION OF TEACHING AS A PROFESSION IN NIGERIA BY SANDWICH STUDENTS OF EKITI STATE UNIVERSITY, ADO-EKITI - Julius O., Adedayo,; Kehinde A, Omotayo,; Margaret F., Ayeni, (IJRDO- Journal of Educational Research, 2017)
This study was a survey type of descriptive research design. It investigated the perception of sandwich students about teaching as a profession in Nigeria. The sample comprised 296 sandwich students, selected using purposive random sampling techniques from Ekiti State University, Ado-Ekiti, Nigeria. The research instrument was a questionnaire. One general question was raised while four null research hypotheses were postulated for the study. The research question was answered using descriptive statistics of mean, percentages and pie chart. The hypotheses were subjected to inferential statistics of x 2 and analysis of variance, all tested at 0.05 level of significance. The findings from this study revealed that most of the sandwich students’ perception of teaching as a profession in Nigeria is negative. While the incoming sandwich students perceived teaching as a profession negatively, the old students agreed that teaching is a profession in Nigeria. Surprisingly, it was found that students who are practicing teachers perceived teaching as a profession in Nigeria negatively contrarily to students who are non-practicing teachers. Based on these findings, recommendations on ways of improving the perception of the students towards regarding teaching as a profession in Nigeria were made.